Harvesting DC current from friction and pressure on silicon-based diodes: from micro to macro devices - Hurtado Torres, Carlos (Curtin University, 2024)
This thesis explores the integration of electrochemistry with semiconductor technology, focusing on the development of DC-generating triboelectric nanogenerators (DC-TENGs) for energy harvesting. Key advancements include silicon functionalized with self-assembled monolayers (SAMs) in Schottky diodes, enhancing energy conversion and wear resistance. Addressing challenges like surface wear and triboelectric effects, it highlights flexoelectricity's role in energy generation. These insights open new venues for more efficient, durable DC-TENGs, potentially impacting fields like wearable electronics, autonomous sensors, and sustainable energy solutions.